Pomen ustrezne socialne vključenosti starejše populacije z vidika dolgotrajne oskrbe - Oven, Alenka (Delavci in delodajalci, 2019)
The rising number of elderly population raises the question of whether the state is responding adequately to the needs of an aging society, which is gradually facing social exclusion. It seems that the government is somehow looking away from the necessary changes in both health and security systems. Social changes require faster adaptation of social security. Due to the view of the current and fast changing society in which the elderly are considered more of "a burden" to society, it is not surprising that relatively few legal regulations are implemented for improving the legal protection of elderly population. The author therefore shows the often overlooked factors of social exclusion of the elderly population and presents de-lege-ferenda for a more systemic approach in this field.
Keywords: dolgotrajna oskrba; long-term care; old age; social exclusion; socialna izključenost; socialna varnost; starost